Implications of the fair processes for financing UHC report for development assistance: reflections and an application of the decision-making principles to PEPFAR - Sara Bennett; Maria W. Merritt (Health Economics, Policy and Law)
The framework presented in the World Bank report Open and Inclusive: Fair processes for Financing Universal Health Coverage effectively connects proposed decision-making principles with practical examples that country governments can use to pursue greater fairness. In this commentary, we consider the suggestion that international development partners might use the report's criteria to examine their own processes. We consider what the report's primary Fair Process principles – equality, impartiality and consistency – imply for development partners. Specifically, we address two questions in turn: (i) how relevant the Fair Processes report is to development assistance for health; (ii) if it is deemed relevant, what practical implications does the report have for how aid works? We address the second question by briefly applying the framework to a particular global health initiative, namely the United States President's Emergency Plan for AIDS Relief (PEPFAR). Our analysis suggests that development partners' additional sets of accountabilities, particularly linked to funding sources, may pose more fundamental challenges to impartiality than to equality and consistency in decision-making processes. A question inviting further examination, then, is how development partners can redesign their processes to optimise impartiality given institutional constraints that bind them independently of the populations they purport to serve.